Measurements of ammonia concentration in buildings of pig enterprises in Greece. - SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ) G. C.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The concentration of ammonia was measured in the air space of 180 houses of 30 pig enterprises in Greece during an 8-month period by using tubes that chemically bind atmospheric ammonia. The mean overall ammonia concentration was 24.6 ppm (10-52 ppm). The mean ammonia concentration according to the age group of the animals was 26.4 ppm in finishing pig houses, 26.2 ppm in growers’ pig houses, 22.6 ppm in flat-deck units and 19.8 ppm in farrowing houses (p<0.05). With regard to the type of the floor, the mean ammonia concentration was 28.0 ppm in concrete-floored houses and 21.4 ppm in slatted-floored ones (p<0.05), and as regards the season of the year, higher concentrations were measured at winter time (27.7 ppm) compared to those seen during spring (24.5 ppm) and summer time (21.1 ppm) (p<0.05). The findings are discussed in relation to the adverse effects that ammonia may have for pig’s health and production.